Pengaruh Motivasi Dan Promosi Jabatan Terhadap Kinerja Pegawai Di Badan Keuangan Daerah Kota Pagaralam - Heri Fitriadi (Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study is to analyze whether there is influence Motivation and Promotion Position on Employee Performance In Regional Financial Agency of Pagar Alam City. This research is a type of explanatory research, because this research intends to explain the variables through hypothesis testing that has been formulated previously. The population of this research is civil servant apparatus with civil servant status and non permanent employee in the regional finance body which amounted to 152 people, with sample used as many as 30 people. Data were analyzed by using multiple linear regression analysis, t-test, and F-test. From the results of multiple regression analysis got the value of the equation Y = 6.265 + 0.056 X1 + 0.744 X2 + e. The equation shows that the coefficient of Motivation (X1) and Promotion of Position (X2) has a direct influence with Performance (Y). Based on the results of the F test (Anova) obtained Fcount> Ftable is 15.096> 3.17, can be interpreted that Motivation and Promotion Position simultaneously significant and proven effect on employee performance. Then Motivation variable obtained t count <0.295 <2.042, mean motivation does not significant effect on employee performance, but variable of Promotion Position to employee performance is obtained t count> ttable that is 5,144> 2,042, means Promotion Position have significant effect to employee performance.